2022
DOI: 10.3390/diagnostics12092077
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Presepsin in Diagnosing Infections in Patients with Liver Cirrhosis and Overt Hepatic Encephalopathy

Abstract: Infections and sepsis represent severe liver cirrhosis (LC) complications and the precipitating factors of hepatic encephalopathy (HE). The early diagnosis and treatment of infections in patients with LC and HE can significantly increase their survival. Presepsin is a serum biomarker evaluated for the early diagnosis of infections and sepsis in the general and cirrhotic populations. This study aimed to evaluate the role of presepsin in the early diagnosis of infections in patients with LC and HE. This prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…In total, 47 patients and 27 healthy individuals were assessed (Figure 1). Patients and controls did not differ in age (49 [44][45][46][47][48][49][50][51][52][53][54][55][56] vs. 48 [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] years; p = 0.372) or sex distribution (male/female: 18/29 vs. 10/17; p = 0.558). The characteristics of patients with cirrhosis are presented in Supplementary Table S1.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In total, 47 patients and 27 healthy individuals were assessed (Figure 1). Patients and controls did not differ in age (49 [44][45][46][47][48][49][50][51][52][53][54][55][56] vs. 48 [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] years; p = 0.372) or sex distribution (male/female: 18/29 vs. 10/17; p = 0.558). The characteristics of patients with cirrhosis are presented in Supplementary Table S1.…”
Section: Resultsmentioning
confidence: 89%
“…The treatment of phagocytes with LPS did not lead to the formation of presepsin, in contrast to treatment with live or dead bacterial cells. This protein is considered to be a diagnostic biomarker for sepsis [34][35][36][37][38]. Therefore, presepsin can be considered as a universal biomarker for the cellular bacterial translocation of both Gram-positive and Gram-negative bacteria, while LPS is a biomarker for both the cellular translocation of whole living or dead Gram-negative bacterial cells and the molecular translocation of single LPS molecules or LPS molecules in fragments of dead Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Presepsin, a protein derived from the co-receptor for bacterial ligands CD14, serves as an effective biomarker of innate immune activation and is useful for early infection diagnosis in cirrhotic patients [ 35 , 36 ]. In a previous study, we demonstrated that presepsin levels ≥2300 pg/mL were associated with infections in ACLF patients [ 12 ]. Furthermore, we found a direct correlation between presepsin levels, disease severity assessed by MELD score, and Child-Pugh class.…”
Section: Discussionmentioning
confidence: 99%
“…Infections in ACLF significantly contribute to higher mortality rates and pose a considerable challenge in the management of this complex condition [ 10 - 12 ]. Patients with ACLF are particularly susceptible to infections due to immune dysregulation, impaired liver function, and systemic complications [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation